A Retrospective Analysis of Non-Attendance (DNA) in Haringey CAMHS: Addressing Barriers to Care and Improving Engagement - Rakesh Sharma (BJPsych Open)
Aims: To evaluate DNA rates and contributory factors within CAMHS to propose interventions that improve appointment adherence and service delivery.